Analysis of reconstructive methods in surgical treatment of small nasal skin defects - Jovic, Marko Stevan (Vojnosanitetski pregled, 2017)
Background. Surgeons often face with the problem when selecting a reconstructive method for nasal skin defects. We have analyzed the functional and aesthetic results of different reconstructive methods used for skin defects in different regions of the nose. Methods. The study involved 44 patients with basocellular carcinoma in nasal area. The nasal skin was divided into four subunits - the tip, the alar lobules, the sidewalls and the dorsum. An average skin defect size was 10 mm. Local flaps and full thickness skin grafts were used in the study. We have analyzed the functional and aesthetic results of different reconstructive methods used for nasal defects in different regions of the nose, twelve months after the surgery. Results. The study has shown that different reconstructive methods produce different functional and aesthetic results in the same nasal subunits and the same reconstructive method produce different results in different nasal subunits. Conclusions. Estimation the postoperative functional and aesthetic characteristics of different reconstructive methods is one of the basic precondition of successful reconstruction.